Objective Structured Assessment of Technical Skills: A Tool to Document Cystoscopic Competency in the Operating Room. (October 2015) - Clark, Dyanna G.; Edenfield, Autumn L.; Swift, Steven
Abstract : PURPOSE: To demonstrate the construct and predictive validity of an objective structured assessment of technical skills (OSATS) checklist for cystoscopy in the operating room. BACKGROUND: The OSATS checklist is a possible tool for documenting residency proficiency in cystoscopy. METHODS: Prospective observational study evaluating residents performing cystoscopy in the operating room over a 4-year period. Residents were scored on two OSATS checklists: assembly and diagnostic cystoscopy. Construct validity was assessed by comparing absolute OSATS scores as well as comparing the percentage of competent residents based on resident year with a Kruskall-Wallis and χ 2 test, respectively. Predictive validity was evaluated by determining the percent of competently performed OSATS checklists subsequent to one competent OSATS completion. RESULTS: One hundred fifty three OSATS evaluations were performed on 30 residents from all 4 years. The median scores and competency scores for assembly and performance of a diagnostic cystoscopy OSATS Checklist scores demonstrated construct validity with P <.001 and P <.0001, respectively. Once competency was obtained for one cystoscope assembly OSATS checklist, 92% of future assembly OSATS were documented as competent. For diagnostic cystoscopy once competency was obtained, 69% of future OSATS checklists were competent. DISCUSSION: The OSATS checklist for assembly and diagnostic cystoscopy demonstrated construct validity. Predicative validity for assembly of a cystoscope is high but less so for performance of a diagnostic cystoscope. This checklist could be used to document proficiency in cystoscopy as part of a milestones portfolio.